Perceptions of Education and Non-Education Students towards the Campus Teaching Program: A Rasch Model Analysis - Isnaini Handayani; Tri Wintolo Apoko; Arum Fatayan; Benny Hendriana; Irdalisa Irdalisa; Isa Faqihuddin Hanif (AL-ISHLAH: Jurnal Pendidikan, 2026)
The Teaching Campus Program, as part of the Merdeka Belajar–Kampus Merdeka (MBKM) initiative, aims to enhance students’ competencies through direct engagement in school environments. However, differences in academic backgrounds may influence how students perceive the program’s contribution to their learning outcomes. This study examines the perceptions of education and non-education students toward the program.This study employed a cross-sectional survey design involving 235 university students who completed the Teaching Campus Program (Batches 2–8) at a private university in Jakarta. Data were collected באמצעות closed- and open-ended questionnaires using a five-point Likert scale. The instrument’s validity and reliability were analyzed using the Rasch Model with Winsteps software, including item fit, person fit, and reliability indices. Descriptive statistics were used to interpret students’ perceptions.The findings indicate that students from education majors reported strong agreement that the program enhances pedagogical, professional, social, and personal competencies relevant to their future careers as teachers. Non-education students also expressed positive perceptions, particularly regarding the development of soft skills such as communication, collaboration, adaptability, and leadership, although the perceived relevance to their academic discipline was lower. Overall, most participants acknowledged the program’s contribution to skill development and professional readiness.These results suggest that the Teaching Campus Program is positively perceived by both groups, with varying degrees of relevance depending on academic background. The program supports competency development and experiential learning, although improvements in implementation and alignment with students’ fields of study are needed.